The WHO-5 Well-Being Index: A Validation Study in People with Infertility - Reza OMANI-SAMANI; Saman MAROUFIZADEH; Amir ALMASI-HASHIANI; Mahdi SEPIDARKISH; Payam AMINI (Iranian Journal of Public Health, 2019)
Background: Infertility is a public health problem and can lead to depressive symptoms. In recent years, the WHO-five Well-being Index (WHO-5) has been used as a screening measure for depression, but study on psychometric properties in people with infertility is scarce. The objective of this study was to examine the reliability and validity of the Persian version of the WHO-5 in people with infertility.